Andrew Allan, Nathan Cohen, and Mavor Moore: Cultural nationalism and the growth of English-Canadian drama, 1945 to 1960. - Dickson Rothwell, Carmel. (University of Ottawa (Canada), 1994)
"Andrew Allan, Nathan Cohen, and Mavor Moore: Cultural Nationalism and the Growth of Canadian Drama 1945-1960" is concerned with the texture and substance of English-Canada's cultural life in the decade and a half following World War II. This thesis represents a case study in English-Canadian cultural nationalism by focussing on the views of three cultural nationalists who believed that the creation of a national theatre could establish a unique Canadian identity and national unity. Essentially, the thesis argues that the early enthusiasm of the period for the potential of Canadian drama, and high culture in general, was thwarted by public apathy, an inferiority complex, the failure of the government to act on the recommendations of the Massey Report, and the omnipresence of television which paved the way for the conquest of mass culture and technology. By simply articulating their concerns about Canadian culture which were validated by the Massey Commission, cultural nationalists demonstrated that a distinct Canadian culture did exist in spite of the growing influence of the United States. (Abstract shortened by UMI.)
Keywords: History, Canadian.